2006
DOI: 10.1631/jzus.2006.b0906
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface

Abstract: Abstract:Objective: To construct a novel kind of nonviral gene delivery vector based on polyethylenimine (PEI) conjugated with polypeptides derived from ligand FGF with high transfection efficiency and according to tumor targeting ability. Methods: The synthetic polypeptides CR16 for binding FGF receptors was conjugated to PEI and the characters of the polypeptides including DNA condensing and particle size were determined. Enhanced efficiency and the targeting specificity of the synthesized vector were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This net positive charge facilitates cell-binding affinity followed by endocytosis. Although, the net positive charge may result in nonspecific binding to cells, it is reported that proper grafting of PEI with targeting ligands such as peptides enabled high specificity to cancer for gene-delivery applications [41]. PEI also shows high buffering capacity over a wide range of pH conditions resulting in flexibility for conjugation reaction with better colloidal stability for nanoparticles in water.…”
Section: Conjugation Of Yo Ncs With Folic Acid Through Polycation Gramentioning
confidence: 99%
“…This net positive charge facilitates cell-binding affinity followed by endocytosis. Although, the net positive charge may result in nonspecific binding to cells, it is reported that proper grafting of PEI with targeting ligands such as peptides enabled high specificity to cancer for gene-delivery applications [41]. PEI also shows high buffering capacity over a wide range of pH conditions resulting in flexibility for conjugation reaction with better colloidal stability for nanoparticles in water.…”
Section: Conjugation Of Yo Ncs With Folic Acid Through Polycation Gramentioning
confidence: 99%
“…In one approach, peptides of short sequence such as KALA, RGD, TAT and so on have been conjugated to the PEI core in order to enhance its targetability, endosomolytic activity or cell penetration. [13][14][15][16] Although PEI 10 kDa suffers from low transfection efficiency, its low toxicity makes it an attractive polymer for modification in order to overcome the shortcomings. Our group has recently reported the structure of a series of alkyl-oligoamine derivatives of PEI 10 kDa (that is, PEI-alkyl and PEI-alkyl-EDA) with enhanced efficiency due to increase in lipophilicity while maintaining low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…710 Other modifications have included altering the surface charge density of PEI 10,11 and adding targeting ligands. 1219…”
Section: Introductionmentioning
confidence: 99%